2000
DOI: 10.1111/j.1528-1157.2000.tb00282.x
|View full text |Cite
|
Sign up to set email alerts
|

Topiramate in Refractory Epilepsy: A Prospective Observational Study

Abstract: Summary:Purpose: This prospective observational study explored the efficacy and tolerability of topiramate (TPM) in patients with refractory epilepsy attending a single outpatient clinic.Methods: One hundred seventy patients (82 men, 88 women, aged 18-75 years) with refractory localization-related (n = 134) or idiopathic generalized epilepsy (n = 36) were started on adjunctive TPM using a standard titration schedule. TPM was introduced after a 3-month prospective baseline, and doses were adjusted according to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
0
4

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 24 publications
6
59
0
4
Order By: Relevance
“…These figures were similar to those reported in our previous TPM study in patients with refractory epilepsy who did not have learning disability (17). Sachdeo et al (8) found a 20.6% median percentage reduction in monthly seizure rate compared with baseline during a double-blind trial of adjunctive TPM in Lennox-Gastaut syndrome.…”
Section: Discussionsupporting
confidence: 80%
“…These figures were similar to those reported in our previous TPM study in patients with refractory epilepsy who did not have learning disability (17). Sachdeo et al (8) found a 20.6% median percentage reduction in monthly seizure rate compared with baseline during a double-blind trial of adjunctive TPM in Lennox-Gastaut syndrome.…”
Section: Discussionsupporting
confidence: 80%
“…dia, doses essas que são significativamente mais baixas que os estudos clínicos à época da publicação 6 . Ritter et al, em estudo com 83 crianças portadoras de epilepsia parcial com ou sem generalização, identificaram que 57% dos pacientes evoluíram com redução no número de crises igual ou superior a 50%; 14% ficaram livres de crise durante 6 meses ou mais de seguimento usando dose média de 9 mg/kg/dia 7 .…”
Section: Discussionunclassified
“…Probably, this drug has a good efficacy on other epilepsies e.g. West's syndrome [54][55][56][57][58][59].…”
Section: Topiramate (Tpm)mentioning
confidence: 98%